2012
DOI: 10.2516/ogst/2011169
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Steady State Method to Water Permeability Measurement in Very Low Permeability Porous Media

Abstract: Résumé -Contribution de la méthode stationnaire dans les mesures des très faibles perméa-bilités à l'eau -Les milieux très peu perméables (k < 10 nD (10 −20 m 2 )) comme les argiles sont étudiés dans le cadre de problématiques très diverses telles que le stockage du CO 2 , les surpressions en forage profond ou le stockage des déchets radioactifs. La caractérisation pétrophysique de ces roches, et notamment la mesure de leur faible perméabilité, est difficile. La technique en laboratoire la plus répandue est ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The accurate hydraulic characterisation of low permeability formations is of high importance to ensure the safety of a geological repository. Hydraulic properties can be estimated by various laboratory and field experiments (Van der Kamp 2001;Yu et al 2013), including empirical methods based on the rock matrix properties (Chapuis and Aubertin 2003), falling head or constant head permeameter tests in laboratory (Boulin et al 2012), and in situ field tests that rely on measurement of pore pressure or water level changes due to tidal natural loading (Bredehoeft 1967;Merritt 2004;Jiang et al 2013) or artificial application of an hydraulic pressure different from the static formation pressure (Neuzil 1982;Butler 1998;Mejías et al 2009). As these methods are carried out from sub-millimetre to hectometre investigation scales, scale dependency can affect the results (Keller et al 1989;Neuzil 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The accurate hydraulic characterisation of low permeability formations is of high importance to ensure the safety of a geological repository. Hydraulic properties can be estimated by various laboratory and field experiments (Van der Kamp 2001;Yu et al 2013), including empirical methods based on the rock matrix properties (Chapuis and Aubertin 2003), falling head or constant head permeameter tests in laboratory (Boulin et al 2012), and in situ field tests that rely on measurement of pore pressure or water level changes due to tidal natural loading (Bredehoeft 1967;Merritt 2004;Jiang et al 2013) or artificial application of an hydraulic pressure different from the static formation pressure (Neuzil 1982;Butler 1998;Mejías et al 2009). As these methods are carried out from sub-millimetre to hectometre investigation scales, scale dependency can affect the results (Keller et al 1989;Neuzil 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The accurate hydraulic characterisation of low permeability formations is of utmost importance to ensure the safety of a geological repository. Hydraulic properties can be estimated by various laboratory and field experiments (Van der Kamp, 2001;Yu et al, 2013), including empirical methods based on the rock matrix properties (Chapuis and Aubertin, 2003), falling head or constant head permeameter tests in laboratory (Boulin et al, 2012), and in situ field tests that rely on measurement of pore pressure or water level changes due to tidal natural loading (Bredehoeft, 1967;Merritt, 2004;Jiang et al, 2013) or artificial application of an hydraulic pressure different from the static formation pressure (Neuzil, 1982;Butler, 1998;Mejias et al, 2009). As these methods are carried out from sub-millimetre to hectometre investigation scales, scale dependency can affect the results (Keller et al, 1989;Neuzil, 1994).…”
mentioning
confidence: 99%
“…Rushing et al [18] found five times greater permeability using the transient approach compared to the steady-state approach. This exhibits differences among permeability calculations under steady-state and transient conditions [22]. Importantly, permeability calculation under both conditions may have considerable errors if the possible CO 2 phase transition through the rock mass is not considered under steady-state conditions [23].…”
Section: Introductionmentioning
confidence: 98%